Pedagogical leadership of the principal and school management of the teachers. IE n°5176 María Reiche Crosse. Puente Piedra. Lima - Gomero Paredes, Miriam Margarita (2023)
The general objective of this research was to determine the relationship that exists between directive leadership and school management in IE N°5176 MARÍA REICHE CROSSE. The type of research used was a basic correlational level with qualitative approaches, non-experimental and cross-sectional design. The population was made up of 55 teachers from IE N°5176 MARÍA REICHE CROSSE in the district of Puente Piedra. The survey technique was used and the instrument was the questionnaire composed of 24 Likert-type questions for each of the study variables, they were validated by expert judgments whose reliability was verified through Cronbach's Alpha whose result of the variable directive leadership = 0.957 and the school management variable = 0.953 It is concluded that directive leadership is significantly related to school management in the Puente Piedra institution mentioned with Spearman's Rho which is 0.761 and a significance value =.000 < 0 .05.